The link between farmgate and world prices in the wake of trade liberalization : the case of Colombia (2000)
This paper evaluates whether trade liberalization in Colombia in 1990-91 increased market integration in 12 commodities that account for some 70 percent of agricultural GDP. Empirical results indicate that for all crops examined, the nature of integration relationships between local and world prices was not altered by reforms. Cotton and cocoa prices retained a high level of association with international markets. Rice, soybeans, oil palm, bananas, and coffee continued to exhibit only some degree of short-term integration but prices continue to diverge from world trends in the long-run. Maize and beef only displayed long-run integration. On the other hand, sugar and sorghum have preserved prices that are effectively isolated from external markets. Generally, results suggest that the majority of tradable agricultural commodities in Colombia have not exhibited high degrees of integration with world markets. This has continued in the post-liberalization period due to the combined effect of strong lobbying groups and policies that have tended to stabilize and/or protect domestic markets, including price bands, import controls, and purchasing agreements with processors.